PSIXOLOGNING SHAXSIY VA PROFESSIONAL RIVOJLANISHI (Modern education and development, 2024)
Ushbu  maqolada , shaxsiy va professional rivojlanishning o‘zaro aloqasi, ular orasidagi bog‘liqlik va bu jarayonlarning ijtimoiy, psixologik va iqtisodiy ahamiyati tahlil qilinadi. В данной статье анализируется взаимосвязь личностного и профессионального развития взаимосвязь между ними и социальная,  психологическая и экономическая значимость этих процессов.  This article analyzes the interconnection between personal and professional development, the relationship between them, and the social, psychological, and economic significance of these processes.